2013
DOI: 10.1017/s0043933913000925
|View full text |Cite
|
Sign up to set email alerts
|

A survey on village chicken production in Kerala state of India

Abstract: The present study was conducted to document the rearing practices of village chicken production in the Northern midlands, agro-ecological zone comprising Kannur and Kozhikode districts of Kerala state, India. Data was generated from 65 and 63 chicken farming families of Kozhikode and Kannur districts respectively. The system of chicken rearing is extensive, with the provision of shelter only during the night. The birds are being managed mostly by women (89.06%). The decision on the sale of birds and eggs is ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…This possibly provides justification of our previous findings (Kumar et al, 2013) of 58 percent of households not maintaining cock in their flock also incubate eggs taking chance of their hens being mated by cocks from neighbourhood. The average land holding per household in the area is only 29.45 cents or nearly 1,200 m 2 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This possibly provides justification of our previous findings (Kumar et al, 2013) of 58 percent of households not maintaining cock in their flock also incubate eggs taking chance of their hens being mated by cocks from neighbourhood. The average land holding per household in the area is only 29.45 cents or nearly 1,200 m 2 .…”
Section: Discussionsupporting
confidence: 80%
“…This result was in sharp contrast with the findings of Vij et al (2007), who reported almost zero mortality from Tellichery chicken of this area. This underlines the need for establishing Government chick nurseries to supply grownup desi birds as emphasized by the farmers of this region earlier (Kumar et al, 2013). In grower stage, a very closer value of 21 percent mortality was documented in Baladi chicken in Saudi Arabia (Yousef and Al-Yousef, 2007).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…To increase the productivity of backyard and rural farming, improved or exotic varieties are being introduced in rural areas or in their breeding traits leading to a dilution of genetic purity of the breeds or a complete replacement of the native germplasm; hence, these breeds are under threat of extinction (Singh, 2009). The studies on indigenous breeds is scanty barring a very few reports (Kumar et al, 2013;Kumar et al, 2016;Rajkumar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%